Mercury distribution in an invasive species (Asystasia gangetica) from Peninsular Malaysia - Chew, W; Yap, C.K; Ismail, A; Zakaria, M.P; Tan, S.G (Universiti Kebangsaan Malaysia, 2012)
In this study, the Hg levels in eight parts of Asystasia gangetica (L.) T. Anderson collected from 14 sites were determined using a Mercury Atomizer MA-1S and a Mercury Detector MD-1. It was found that the ranges for all the parts were 3.21-18.2 μg/kg dry weight for flowers, 1.29-11.2 μg/kg dry weight forstalks, 0.32- 29.4 μg/kg dry weight for seeds, 0.87-10.2 μg/kg dry weight for pericarps, 1.45-18.1 μg/kg dry weight for remainders, 11.8-68.2 μg/kg dry weight for leaves, 0.73-20.9 μg/kg dry weight for stems, and 3.40-33.1 μg/kg dry weight for roots. The overall Hg accumulation pattern in decreasing concentrations was leaf > root > flower > flower remains > stalk > stem > pericarp > seed. This study provided the background levels of Hg in this non-native invasive weed species in Malaysia. However, further studies